The theory behind, and the challenges of, conserving nature's stage in a time of rapid change. Issue 3 (28th April 2015) - Lawler, Joshua J.; Ackerly, David D.; Albano, Christine M.; Anderson, Mark G.; Dobrowski, Solomon Z.; Gill, Jacquelyn L.; Heller, Nicole E.; Pressey, Robert L.; Sanderson, Eric W.; Weiss, Stuart B.
Abstract: Most conservation planning to date has focused on protecting today's biodiversity with the assumption that it will be tomorrow's biodiversity. However, modern climate change has already resulted in distributional shifts of some species and is projected to result in many more shifts in the coming decades. As species redistribute and biotic communities reorganize, conservation plans based on current patterns of biodiversity may fail to adequately protect species in the future. One approach for addressing this issue is to focus on conserving a range of abiotic conditions in the conservation‐planning process. By doing so, it may be possible to conserve an abiotically diverse "stage" upon which evolution will play out and support many actors (biodiversity). We reviewed the fundamental underpinnings of the concept of conserving the abiotic stage, starting with the early observations of von Humboldt, who mapped the concordance of abiotic conditions and vegetation, and progressing to the concept of the ecological niche. We discuss challenges posed by issues of spatial and temporal scale, the role of biotic drivers of species distributions, and latitudinal and topographic variation in relationships between climate and landform. For example, abiotic conditions are not static, but change through time—albeit at different and often relatively slow rates. In some places, biotic interactions play a substantial role in structuring patterns of biodiversity, meaning that patterns of biodiversity may be less tightly linked to the abiotic stage. Furthermore, abiotic drivers of biodiversity can change with latitude and topographic position, meaning that the abiotic stage may need to be defined differently in different places. We conclude that protecting a diversity of abiotic conditions will likely best conserve biodiversity into the future in places where abiotic drivers of species distributions are strong relative to biotic drivers, where the diversity of abiotic settings will be conserved through time, and where connectivity allows for movement among areas providing different abiotic conditions. Abstract : Los Obstáculos y la Teoría detrás de la Conservación del Estado de la Naturaleza en Tiempos de Cambios Rápidos Resumen: La mayoría de los planes de conservación a la fecha se han enfocado en proteger a la biodiversidad de hoy bajo la suposición de que será la biodiversidad de mañana. Sin embargo, el cambio climático contemporáneo ya ha resultado en cambios de distribución de algunas especies y se tiene proyectado que resulte en muchos cambios más en las siguientes décadas. Conforme las especies se redistribuyen y las comunidades bióticas se reorganizan, los planes de conservación con base en los patrones actuales de biodiversidad pueden fallar en proteger adecuadamente a las especies en el futuro. Una estrategia para dirigirse a este tema consiste en enfocarse en la conservación de una gama de condiciones abióticas durante el proceso de planeación de la conservación. Al hacer esto, puede ser posible conservar una "etapa" de diversidad abiótica sobre la cual actuará la evolución y sustentará a muchos actores (biodiversidad). Revisamos los apuntalamientos fundamentales del concepto de conservación de la etapa abiótica, comenzando con las observaciones iniciales de von Humboldt, quien mapeó la concordancia de las condiciones abióticas y la vegetación; y progresando hasta el concepto de nicho ecológico. Discutimos los obstáculos impuestos por los temas de escala espacial y temporal, el papel de los conductores bióticos de la distribución de las especies, y la variación latitudinal y topográfica en las relaciones entre el clima y los accidentes geográficos. Por ejemplo, las condiciones abióticas no son estáticas, sino que cambian con el tiempo—no obstante a tasas diferentes y frecuentemente lentas. En algunos lugares, las interacciones bióticas juegan un papel sustancial en los patrones de estructuración de la biodiversidad, lo que significa que los patrones de la biodiversidad pueden estar menos relacionados con la etapa abiótica. Más allá, los conductores abióticos pueden cambiar con la posición topográfica y la latitud, lo que significa que la etapa abiótica necesitará definirse diferentemente en lugares distintos. Concluimos que proteger una diversidad de condiciones abióticas probablemente conserve de mejor manera a la biodiversidad hacia el futuro en lugares donde los conductores abióticos de la distribución de especies son fuertes en relación con los conductores bióticos, donde la diversidad de configuraciones abióticas se mantendrán a lo largo del tiempo, y donde la conectividad permita movimiento entre áreas que proporcionan diferentes condiciones abióticas .